Effect of carbon emissions disclosure & CSR theme on firm value with firm reputation as moderating variable - Meyliana, Meyliana; Sudibyo, Yvonne Augustine (Technium Sustainability, 2022)
The purpose of this study is to examine the effect of carbon emissions disclosure and CSR themes disclosure on firm value as measured by price to book value ratio (PBV). Furthermore, this study also investigates the magnitude of a firm reputation as a moderating variable of relationship between these factors. This study uses a quantitative descriptive approach to provide evidence of the effect of carbon disclosure and CSR themes on firm value. The findings show carbon emission disclosure affects firm value while CSR themes disclosure does not. Testing with the moderating variable of firm reputation produces a sig value greater than 0.05. This indicates that firm reputation is not a moderating variable for the relationship between CSR themes disclosure and carbon emissions disclosure on firm value.